Islamic Scholarship in The Malay World: The Multifaceted Contributions of Ulama - Abdurrahman Raden Aji Haqqi; Achmad Yani; Hjh. Rasinah binti Hj Ahim; Hjh Sri Rahayu Nurjanah binti Hj Dollah; Hjh. Sarinah binti Hj Yahya; Mariam binti Abdul Rahman; Hjh Masuriyati binti Hj Yahya; Artini binti Hj Timbang (International Journal of Nusantara Islam, 2023)
This study explores the extensive roles and contributions of Ulama (Islamic scholars) in the Malay Archipelago, with a focus on their impact in the fields of Islamic economics, sciences, and mathematics. The research aims to illuminate how Ulama have shaped various aspects of Islamic culture, education, and intellectual thought in the region. A comprehensive literature review was conducted, examining historical texts, manuscripts, and scholarly works related to the Ulama. The study employed qualitative analytical approaches to assess the contributions of Ulama in the Malay Archipelago. Findings indicate that Ulama significantly influenced Islamic economics by aligning economic practices with Sharia principles, emphasizing justice and ethical compliance. In scientific and mathematical fields, Ulama integrated complex mathematical concepts with Islamic teachings, contributing to the advancement of these disciplines. The educational impact of Ulama, particularly through the pondok system, promoted self-reliance and entrepreneurship, while their cultural synthesis effectively combined Islamic knowledge with local traditions. The Ulama’s roles extended beyond religious instruction, encompassing broader societal, economic, and intellectual domains. Their contributions not only facilitated the spread of Islam but also respected and preserved local customs. The study underscores the Ulama’s enduring influence in shaping the educational and intellectual landscape of the Malay Archipelago.